2007
DOI: 10.1007/s00056-007-0720-3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Temporomandibular Disorders in Young Adults: Indication for Systematic Temporomandibular Joint Screening

Abstract: Should clinical TMD become apparent during orthodontic treatment, the patient might attribute it to the therapy, rather than to the subclinical disorder at baseline. It thus makes therapeutic and forensic sense to carry out systematic TMJ-screening in all adult patients prior to orthodontic treatment, in order to identify patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Therefore, the early stages of a disorder may go undiagnosed and remain untreated. According to Jensen & Ruf studies 2 almost every third subjects with subclinical TMD developed clinical TMD over a 2.4- year period. They also emphasize that it would be deliberate to carry out systematic TMJ-screening in all adult patients prior to orthodontic treatment, in order to identify patients at risk.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the early stages of a disorder may go undiagnosed and remain untreated. According to Jensen & Ruf studies 2 almost every third subjects with subclinical TMD developed clinical TMD over a 2.4- year period. They also emphasize that it would be deliberate to carry out systematic TMJ-screening in all adult patients prior to orthodontic treatment, in order to identify patients at risk.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical awareness of a multidimensional association between CeH and TMD could influence future treatment . Detecting signs of a preclinical TMD is crucial to identify patients at risk for a clinically manifest TMD . In such a situation, TMD can exacerbate already existing headache via an overlap of innervation involving the trigeminal nerve .…”
Section: Discussionmentioning
confidence: 99%
“…This stresses the need for thorough analysis of TMJ on three representative layers in an oblique sagittal line in order to avoid doubts about the usefulness of MRI findings (Bumann & Lotzmann, 2002), which still poses a problem of how to interpret the disc image with respect to its physiological position or anterior displacement (Petersson, 2010). Jensen & Ruf (2007) followed subclinical and clinical symptoms of TMD which were detected and managed by MFA in a group of students. In a period of 2.4 years on average, an increase of those with clinical signs of TMD occurred.…”
Section: Epidemiology Of Tmd and The Use Of Mrimentioning
confidence: 99%
“…The need for pre-treatment diagnostics and treatment planning was stressed which leads to a successful outcome of fixed orthodontic treatment as well as to the avoidance of complications related to possible exacerbation of TMD symptoms. Jensen & Ruf (2007) showed that during a long-term orthodontic treatment, significant development of TMD is not to be expected. Likewise, the transformation of subclinical signs into clinical signs of TMD can be expected, which should not be associated with the course of possible orthodontic treatment.…”
Section: Implications Of Orthodontic Treatment On Tmdmentioning
confidence: 99%